2018
DOI: 10.1128/aem.00978-18
|View full text |Cite
|
Sign up to set email alerts
|

Poisoning with Soman, an Organophosphorus Nerve Agent, Alters Fecal Bacterial Biota and Urine Metabolites: a Case for Novel Signatures for Asymptomatic Nerve Agent Exposure

Abstract: The experimental pathophysiology of organophosphorus (OP) chemical exposure has been extensively reported. Here, we describe an altered fecal bacterial biota and urine metabolome that follows intoxication with soman, a lipophilic G class chemical warfare nerve agent. Non-anaesthetized Sprague-Dawley male rats were subcutaneously administered soman at 0.8 (sub-seizurogenic) or 1.0 (seizurogenic) of the median lethal dose (LD) and evaluated for signs of toxicity. Animals were stratified based on seizing activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 51 publications
(67 reference statements)
2
9
0
Order By: Relevance
“…Soman. exposure increased in the relative abundance of Proteobacteria and Cyanobacteria 72 hours post exposure (Getnet et al, 2018). This was also observed in the current study, specifically at 48 hours post-DFP exposure.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Soman. exposure increased in the relative abundance of Proteobacteria and Cyanobacteria 72 hours post exposure (Getnet et al, 2018). This was also observed in the current study, specifically at 48 hours post-DFP exposure.…”
Section: Discussionsupporting
confidence: 88%
“…Notably, DFP-exposed animals eat less in the 2-3 days following DFP intoxication, and therefore lose bodyweight. A number of bacteria have been found to contain genes implicated in metabolism of OPs, which could explain the increase in abundance of Proteobacteria and Cyanobacteria (Karpouzas and Singh, 2006;Getnet et al, 2018). Future studies could determine if any of the genera/species identified in this study are capable of OP metabolism.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In the latter study, they also administered 3 mg/kg MDZ but at 40 min post-soman. The other three soman studies without pretreatment tested the efficacy of diazepam (10 mg/kg) with 0.8-1.0 LD 50 soman (instead of 1.2 LD 50 ), however, the mortality details were not reported (Schultz et al, 2012(Schultz et al, , 2014Getnet et al, 2018). Recently, we also demonstrated in the rat DFP model that midazolam is more effective than diazepam in preventing mortality (Gage et al, 2021).…”
Section: Discussionmentioning
confidence: 98%